THE RELATIONSHIPS BETWEEN THE FINANCIAL HEALTH AND FINANCIAL PERFORMANCE OF LIFE INSURANCE FIRMS: AN EMPIRICAL EVIDENCE FROM INDONESIA - Toto Sugiharto; Novita Sulistiowati; Rina Nofiyanti (Universitas Gunadarma, 2019)
Financial performance is of importance for life insurance firms. It is affected by various factors including financial health which is measured by risk-based capital, technical reserve and equity. The study aims at analyzing the effect of these financial health measures on the financial performance of life insurance firms. Secondary data which include financial performance (i.e., return on assets), risk-based capital, technical reserve and equity of thirty three life insurance firms for the periods of 2011-2016 was used. Panel data regression analysis was performed to analyze the obtained data. Financial performance was affected by risk-based capital, technical reserves and equity in different directions. Financial performance of life insurance firms increases with low risk-based capital and technical reserves, but decreases with high equity.